AI in Robotics: Advancements, Applications and Challenges (Journal of Information Technology and Digital World, 2023)
The development, uses, and difficulties of artificial intelligence (AI) in the field of robotics are examined in this research study. Robotics has been transformed by the use of AI approaches, which allow robots to carry out difficult tasks in an adaptive and independent manner. This article gives a general overview of the many AI methods are used in robotics, including planning/control, computer vision, natural language processing, and machine learning. The numerous uses of AI in robotics, including industrial automation, service robots, autonomous cars, space exploration, and agriculture, are further discussed. The report also discusses issues related to safety and ethics, collaboration between humans and robots, adaptation and uncertainty, data constraints, and explainability/transparency. This research study seeks to contribute to the comprehension and development of AI in robotics by highlighting the current state, prospective future directions, and opportunities in the field.
Keywords: Robotics; Artificial Intelligence; machine learning; Natural Language Processing